2011
DOI: 10.1590/s0103-50532011001200017
|View full text |Cite
|
Sign up to set email alerts
|

Production of indole-3-acetic acid in the culture medium of microalga Scenedesmus obliquus (UTEX 393)

Abstract: O acido indolacético (IAA) é uma auxina natural e um dos principais reguladores do crescimento de plantas superiores. A quantidade de ácido indolacético extracelular produzida pela cultura de microalga verde Scenedesmus obliquus foi estabelecida por cromatografia líquida de alta eficiência (HPLC). Avaliou-se o efeito de três variáveis de processo na produção de IAA extracelular nestas culturas usando planejamento fatorial 2 3 para uma metodologia de screening. As variáveis de planejamento experimental foram ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 16 publications
0
8
1
Order By: Relevance
“…IAA has also been detected in various microalgal chlorophytes, including Chlorella pyrenoidosa and Scenedesmus spp. (Mazur et al, 2001 ; Prieto et al, 2011 ). These studies have found evidence corroborating the hypothesis that evolution of auxin biosynthesis predates the divergence of land plants and some algal taxa.…”
Section: Introductionmentioning
confidence: 99%
“…IAA has also been detected in various microalgal chlorophytes, including Chlorella pyrenoidosa and Scenedesmus spp. (Mazur et al, 2001 ; Prieto et al, 2011 ). These studies have found evidence corroborating the hypothesis that evolution of auxin biosynthesis predates the divergence of land plants and some algal taxa.…”
Section: Introductionmentioning
confidence: 99%
“…According to Mishra et al (1999) the use of extragenous fitohormon shows positive response to the formation of root nodule. The indole acetic acid (IAA) is a natural auxin and one of the main growth regulators in higher plants (Prieto C et al, 2011). Plants synthetizing higher IAA showed a significant increase in shoot fresh weight and upregulation of nitrogenase gene (Bianco et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…[13,18], Scenedesmus sp. [12,20], and Acutodesmus dimorphus [21] has been reported recently. Phytohormones are usually present in microalgae at very low concentration with various structures, and thus determination of phytohormone levels in microalgae is extremely challenging.…”
Section: Introductionmentioning
confidence: 95%
“…It has been reported that microalgae could produce exogenous [12] and endogenous phytohormones [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%